02 PENINGKATAN PENDAPATAN KELOMPOK WANITA TANI (KWT) MELALUI PEMANFAATAN LAHAN PEKARANGAN DI DESA LEKOPANCING KECAMATAN TANRALILI DI KABUPATEN MAROS (Studi Pada Anggota Kelompok Wanita Tani di Desa Lekopancing) - Jurnal Agribis; Irwan Irwan; Zulkifli Zulkifli (Jurnal Agribis, 2018)
The purpose of this study was to determine community income through the use of the plot of land and to determine the potential of the yard as a source of additional income for the community in the village of Lekopaccing, Tanralili sub-district, Maros Regency. This study uses quantitative research methods with a population of 60 households / 120 people and a sample of 21 people using the Slovin formula, in data analysis using the percentage analysis method with the formula P = F / N x 100 and the income formula using ? = TR - TC for Data collection using questionnaires, observations, interviews, and documentation. Based on the results of research and discussion, it can be concluded that there are many forms of land use developed by the community on the plots owned for example for agriculture or plantations such as banana, kale, spinach, long beans and chillies. Livestock such as cattle, chicken and duck farms. the use of the plot of land owned is very influential on increasing the income of the people in Lekopancing Village Based on the respondent's answer, after utilizing the yard the average income of the community increased by> Rp. 100,000 - Rp. 500,000 per month. The total community income from the use of the plot of land, namely vegetables (kale, long beans, spinach) is Rp.45,000 / month. Total income / income from raising native chickens is Rp.1,160,000 / 1 year. Total income / acceptance of farmers from raising ducks is Rp. 3. 556,000 / 1 year and the total income / income of farmers from raising cattle is Rp. 13,100,000 / 3 years.